Coelimycin Synthesis Activatory Proteins Are Key Regulators of Specialized Metabolism and Precursor Flux in Streptomyces coelicolor A3(2) - Bednarz, Bartosz; Millan-Oropeza, Aaron; Kotowska, Magdalena; Świat, Michał; Quispe Haro, Juan J.; Henry, Céline; Pawlik, Krzysztof (Frontiers in Microbiology, 2021)
Secondary metabolites are industrially-relevant agents but also serve as signaling molecules in intra-species and even inter-kingdom interactions. In the antibiotic-producing Streptomyces, their biosynthetic gene clusters are activated by the respective Streptomyces antibiotic regulatory proteins (SARPs), encoded within each cluster. Coelimycin is the earliest, colored secondary metabolite synthesized in the life cycle of the model organism Streptomyces coelicolor A3(2). Deletion of its two SARP activators cpkO and cpkN not only abolished coelimycin synthesis but also resulted in dramatic changes in the production of the later, stationary-phase antibiotics by deregulation of quorum sensing, precursor flux and stress response, as shown by label-free, bottom-up shotgun proteomics. Detailed profiling of promoter activities demonstrated that CpkO is the upper-level cluster activator that induces CpkN, while CpkN activates type II thioesterase ScoT, necessary for coelimycin synthesis. What is more, we show that cpkN is regulated by quorum sensing gamma-butyrolactone receptor ScbR.